Estimation of annual probabilities of changing disability levels in Australians with relapsing-remitting multiple sclerosis. (November 2019) - Ahmad, Hasnat; van der Mei, Ingrid; Taylor, Bruce V; Lucas, Robyn M; Ponsonby, Anne-Louise; Lechner-Scott, Jeannette; Dear, Keith; Valery, Patricia; Clarke, Philip M; Simpson, Steve; Palmer, Andrew J
Background: Transition probabilities are the engine within many health economics decision models. However, the probabilities of progression of disability due to multiple sclerosis (MS) have not previously been estimated in Australia. Objectives: To estimate annual probabilities of changing disability levels in Australians with relapsing-remitting MS (RRMS). Methods: Combining data from Ausimmune/Ausimmune Longitudinal (2003–2011) and Tasmanian MS Longitudinal (2002–2005) studies ( n = 330), annual transition probabilities were obtained between no/mild (Expanded Disability Status Scale (EDSS) levels 0–3.5), moderate (EDSS 4–6.0) and severe (EDSS 6.5–9.5) disability. Results: From no/mild disability, 6.4% (95% confidence interval (CI): 4.7–8.4) and 0.1% (0.0–0.2) progressed to moderate and severe disability annually, respectively. From moderate disability, 6.9% (1.0–11.4) improved (to no/mild state) and 2.6% (1.1–4.5) worsened. From severe disability, 0.0% improved to moderate and no/mild disability. Male sex, age at onset, longer disease duration, not using immunotherapies greater than 3 months and a history of relapse were related to higher probabilities of worsening. Conclusion: We have estimated probabilities of changing disability levels in Australians with RRMS. Probabilities differed between various subgroups, but due to small sample sizes, results should be interpreted with caution. Our findings will be helpful in predicting long-term disease outcomes and in health economic evaluations of MS.